2005
DOI: 10.1016/j.meatsci.2005.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Lamb meat quality of two breeds with protected origin designation. Influence of breed, sex and live weight

Abstract: Lamb meat quality of two Portuguese products was examined. The influences of slaughter weight, sex and breed on eating quality were evaluated. Data were obtained from 72 lambs of two different breeds with protected designation origin. In accord with the normal slaughter weight in the region three classes were considered: A: 9-14 kg live weight; B: 14-19 kg live weight and C: 19-24 kg live weight. pH of M. longissimus thoracis et lumborum muscle (MTL) was measured 1 h and 24 h after slaughter. Meat colour was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
1
18

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 24 publications
(45 reference statements)
12
51
1
18
Order By: Relevance
“…were small compared to the impacts of production site, year, slaughter group and intrinsic muscle factors, and compared to previously reported values (Hopkins & Fogarty, 1998;Teixeira et al, 2005). The effects of sire type on meat redness, yellowness, hue and chroma were not accounted for by differences in muscle myoglobin, iron or ICDH activity, as was the effect on meat lightness.…”
Section: Accepted M Manuscriptmentioning
confidence: 49%
See 2 more Smart Citations
“…were small compared to the impacts of production site, year, slaughter group and intrinsic muscle factors, and compared to previously reported values (Hopkins & Fogarty, 1998;Teixeira et al, 2005). The effects of sire type on meat redness, yellowness, hue and chroma were not accounted for by differences in muscle myoglobin, iron or ICDH activity, as was the effect on meat lightness.…”
Section: Accepted M Manuscriptmentioning
confidence: 49%
“…Certain production factors such as lamb breed, slaughter weight and nutrition influence fresh lamb meat colour (Hopkins & Fogarty, 1998;Martıńez-Cerezo et al, 2005;Priolo, Micol, Agabriel, Prache, & Dransfield, 2002;Ripoll, Joy, Muñoz, & Albertí, 2008;Teixeira, Batista, Delfa, & Cadavez, 2005). Hopkins and Fogarty (1998) reported that colourimetric measures of meat L*, a* and b* differed by up to 1.6, 1.1 and 0.9 units between lamb breeds, while Teixeira et al (2005) reported smaller differences of 0.3, 0.6 and 0.7 units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juárez et al (2009) observed an increase (p<0.01) in myoglobin (3.09 to 4.01 mg/g), low (p<0.01) luminosity (45.10 to 40.19 L * ) and increased (p<0.01) redness (7.35 to 9.79 a * ) with increasing (p<0.01) slaughter weight of Grazalema Merino sheep breed. In another study, Teixeira et al (2005) identified a reduction (p<0.05) in L * of 40.0 ± 0.55 to 39.0 ± 0.54 when slaughter weight increased from 9-14 to 19-24 Kg.…”
Section: Age and Body Weightmentioning
confidence: 89%
“…The differences in the degree of muscularity, age and physiological action of the calpain-calpastatin enzyme complex are mainly responsible for the variation in tenderness of lamb meat (Thompson et al, 2006). Teixeira et al (2005) showed objective differences (p<0.01) in meat tenderness between Bragançano (7.8 Kg/cm 2 ) and Mirandesa (6.8 Kg/cm 2 ) sheep breeds. According to the authors, the sensory panel also identified differences (p<0.05) in hardness, assigning scores of 4.1 to Bragançano and just 2.8 for Mirandesa.…”
Section: Breedmentioning
confidence: 97%